The paper trail : an unexpected history of the world's greatest invention - Monro, Alexander (London : Allen Lane, an imprint of Penguin Books, 2014)
This is the story of how you came to be holding this book, how you came to be following its printed words across dozens of pages, pages made not from bamboo, silk, parchment or papyrus, but from paper. The emergence of paper in the imperial court of Han China brought about a revolution in the transmission of knowledge and of ideas. For over two millennia, it has allowed ideas, religions, philosophies and propaganda to spread around the world with ever greater ease. Paper was the first writing surface sufficiently cheap, portable and printable for books, pamphlets, prints and journals to be mass-produced and to travel widely. It enabled an ongoing dialogue between communities of scholars who could now engage with each others ideas across continents and years. The Paper Trail traces the westward voyage of this ground-breaking invention; beginning with the Buddhist translators responsible for the spread of paper across China, Japan, Korea and Vietnam. It describes the theologians, scientists and artists who used paper to create the intellectual world of the Abbasid Caliphate, and journeys with the missionaries and merchants who carried it along the Silk Road. Paper finally reached Europe in 1276 and was indispensable to the scholars and translators who manufactured the Renaissance and Reformation from their desks. Paper created a world in which free thinking could flourish, and brought disciplines from science to music into a new age: the paper age. Paper still surrounds us in our everyday lives - on our desks, wrapping our food, in our wallets. It has become universal, and also supremely disposable. But is the age of paper coming to an end? This is the story of how a simple Chinese invention has wrapped itself around our world, with history's most momentous ideas etched upon its surface.
Tracing Paper -- Alpha and Omega -- Preparing the Soil -- Genesis -- At the Margins -- Paper Rain -- Papyrocracy -- The Handover -- Bibliophiles -- Building Books -- A New Music -- Bagdatixon and its Ologies -- A Continent Divides -- Translating Europe -- A New Dialogue -- By the Cartload.
Includes bibliographical references (pages 329-348) and index.
Text in English.
Keywords: Papermaking -- History; Paper -- History